Immigrants in the Grand Duchy of Luxembourg and Its Public Security - Olbrycht, Paweł (Historia i Polityka, 2021)
The Grand Duchy of Luxembourg is one of the smallest European countries – both in terms of area and population. As in the case of the so-called European micro-states (with less than 500,000 inhabitants – Luxembourg alone has slightly more), it is characterized by a high economic level, especially the living standards of its inhabitants. As the Organisation for Economic Co-operation and Development’s statistical data show (official OECD website), the Grand Duchy of Luxembourg is the wealthiest Member State of the European Union in terms of average annual income per capita (gross domestic product per capita). Due to this fact, foreigners-immigrants continuously come to this country by seeking better living conditions there. It was, therefore, reasonable to explore how this high proportion of immigrants in Luxembourg’s society influences the public security of that country. Luxembourg has one of the highest economic immigration rates in Europe, the number of its citizens is continually growing, and yet the crime rates are among the lowest in the world. The article aims to explore the impact of the presence of many immigrants in the Grand Duchy of Luxembourg on public security of that country. The article focuses on the main threat to public safety, i.e., crime – in the analysed case: the crime committed by foreigners-immigrants. The main research problem took the form of the question: To what extent does the presence of a significant number of immigrants affect the public safety of the Grand Duchy of Luxembourg? The main hypothesis took the form of the assumption that the presence of large numbers of immigrants does not have a significant adverse effect on the public safety of the Grand Duchy of Luxembourg. The adopted research method was the analysis of statistical data using the technique of content analysis (desk research). World Bank statistics were used as the primary source of information, while articles from scientific journals and reports from Luxembourg public administration bodies as supplementary sources. To deepen the exploration and understanding of the migration conditions of the Grand Duchy of Luxembourg, the article presents its history as well as economic and social characteristics. The research was carried out as part of the Research Project No. 146/WNB/65/DzS called: “The Migration Policy of the Republic of Poland as an Indicator of Its Internal Security”, carried out at Faculty of Security Studies of General Tadeusz Kościuszko Military University of Land Forces (Wrocław, Poland).